High school musical 3 : senior year : the junior novel - Grace, N. B.; Barsocchini, Peter, 1952- (New York : Disney Press, 2008)
Seniors Troy and Gabriella, facing the prospect of college apart, join with their classmates in staging a spring musical that looks back on their high school experiences and forward to the future. Includes photographs from the movie.
"Based on the characters created by Peter Barsocchini.".
"Based on the screenplay written by Peter Barsocchini.".
6.7
3-6
Keywords: High schools -- Juvenile fiction; Musicals -- Juvenile fiction; High schools -- Fiction; Musicals -- Fiction; High schools -- Fiction; Movie novels; Musicals -- Fiction; Movie novels